PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4 – 5 TAHUN DI PAUD TUNAS HARAPAN TULUNGAGUNG - Kartika Rinakit Adhe (Jurnal CARE (Children Advisory Research and Education), 2013)
The purpose of this study was to determine and describe the results of the application of contextual learning approach to the cognitive development of children aged 4-5 years in PAUD Tunas Harapan Tulungagung. This research uses a pre-experimental research design with pre-test and post-test group design, with the design of a group of subjects. Data collection methods used were observation. The subjects of this study grader A total of 12 student. The data analysis technique used is the technique of non-parametric statistical analysis using the Wilcoxon test. From the above results, it is known that T_hitung <T_tabel (0 <14). This means that the research hypothesis states that "the application of contextual learning approach to deliver results to the cognitive development of children in early childhood vBulletin Tunas Harapan" is acceptable.